Dry sliding wear behaviour of ZrB2-based ceramics: Self-mated and cross coupling with alumina. Issue 14 (November 2022) - Sciti, Diletta; Guicciardi, Stefano; Zoli, Luca; Failla, Simone; Melandri, Cesare
Abstract: Systematic dry sliding wear tests with monolithic ZrB2 and Al2 O3 pins coupled to ZrB2, ZrB2 -20 vol% SiC and Al2 O3 discs were carried out in a disc-on-pin configuration. The steady state friction of ZrB2 self-mated or cross coupled with Al2 O3 was about 1.1. Self-mated monolithic ZrB2 discs worn about three orders of magnitude more than self-mated Al2 O3 discs. ZrB2 pin wear rate was almost double when coupled to ZrB2 or ZrB2 -20 vol% SiC discs than when coupled to Al2 O3 discs. The wear track of ZrB2 -based materials showed an oxygen increment due to humidity-driven tribo-reaction. In all the systems, the main wear mechanisms observed were microfracture and abrasion. Numerical calculations and fracture models were employed to describe the wear mechanisms. By nanoindentation tests on worn and unworn areas, a significant lower hardness of the debris layer formed when ZrB2 materials were involved.